ANALISIS TEKNIK MRI SEKUEN DUAL ECHO DALAM MEMVISUALISASIKAN KELAINAN PADA LIVER DI RSUD BAKTI PAJAJARAN - Eka Lidyana (Poltekkes Kemenkes Semarang, 2026)
Clinically, Magnetic Resonance Imaging (MRI) is a diagnostic imaging modality that does not use ionizing radiation and has a high capability for visualizing soft-tissue details, including the liver. In this matter, the dual-echo sequence (in-phase and out-of-phase) is a technique that utilizes the chemical shift phenomenon between water and fat, thereby enabling the identification of hepatic steatosis and the differentiation of fat-containing and non-fat-containing lesions. For this reason, this technique has become an important component in the evaluation of liver diseases with increasing prevalence, such as fatty liver disease and other hepatobiliary disorders. This research aims to analyse the implementation of the dual-echo MRI sequence in visualizing any liver abnormalities undertaken at Bakti Pajajaran Regional General Hospital, as well as to assess image quality and characterize the differences between in-phase and out-of-phase images. This research was conducted from September to November 2025 using a qualitative descriptive analytic method, involving among the other things observation of the examination process, in-depth interviews with radiographers and radiologists, and analysis of MRI images. As for the research population, it consisted of 44 patients undergoing MRCP examinations, and the aforementioned 14 patients who underwent imaging with the dual-echo sequence were accordingly selected as the research sample using purposive sampling. Furthermore, the research instruments included a 3-Tesla MRI scanner, observation sheets, interview guidelines, and DICOM viewer software. Primary data consisted of interview results with radiologists and radiographers, while secondary data included acquisition parameters, image quality assessments, and documentation of MRI findings. Data processing was conducted by collecting, selecting, organizing, and categorizing the data according to the research themes. Data analysis focused on the ability of the dual-echo sequence to depict fatty liver, focal lesions, diffuse liver abnormalities, and biliary abnormalities, using a qualitative approach that included data reduction, data presentation, and conclusion drawing. The results of the research indicate that the dual-echo sequence is highly effective in detecting hepatic steatosis, as demonstrated by a distinct signal drop on out-of-phase images. Non–fat-containing lesions, such as solid masses in the distal common bile duct (CBD) and hepatic cysts, did not show signal loss, allowing them to be clearly differentiated from fat-containing lesions. In addition, this technique provides supplementary information on hepatobiliary abnormalities, such as ductal dilatation and CBD stones, although it is not the primary MRCP sequence. Overall, image quality was good, influenced by consistent acquisition parameters and the successful implementation of breath-hold techniques. Ultimately, radiologists reported that this sequence is highly useful as an adjunct examination for assessing liver tissue composition.